1996
DOI: 10.1159/000292266
|View full text |Cite
|
Sign up to set email alerts
|

Plasma Nitric Oxide Levels in Pregnant Patients with Preeclampsia and Essential Hypertension

Abstract: Nitric oxide (NO) production may be an important causal factor in hypertensive disorders during pregnancy. The plasma concentrations of NO2––+NO3––, stable metabolites of NO, were measured in 70 nonpregnant women, 323 normotensive pregnant women, 23 pregnant patients with preeclampsia, and 7 pregnant patients with essential hypertension. The normotensive women had higher plasma concentrations (30.0 ± 0.6 µmol/l) than nonpregnant women (18.3 ± 1.0 µmol/l; p < 0.0001).… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
41
0

Year Published

1999
1999
2012
2012

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(43 citation statements)
references
References 18 publications
2
41
0
Order By: Relevance
“…With respect to the comparison of nitric oxide synthesis between nonpregnant and pregnant women in previous studies [11,18], serum nitrite or plasma nitrite and nitrate concentrations in normotensive pregnant women were significantly elevated as compared with those in the normotensive nonpregnant women. However, Smarason et al [22] reported that there is no significant difference in serum nitrate concentration between healthy pregnant women and nonpregnant controls.…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…With respect to the comparison of nitric oxide synthesis between nonpregnant and pregnant women in previous studies [11,18], serum nitrite or plasma nitrite and nitrate concentrations in normotensive pregnant women were significantly elevated as compared with those in the normotensive nonpregnant women. However, Smarason et al [22] reported that there is no significant difference in serum nitrate concentration between healthy pregnant women and nonpregnant controls.…”
Section: Discussionmentioning
confidence: 78%
“…Yallampalli et al [10] show that an L-arginine-nitric oxide relaxation system is present in the rat uterus and it inhibits contractility during pregnancy but not during labor. Plasma nitrite and nitrate concentrations in normotensive pregnant women was constant throughout pregnancy, and significantly elevated as compared with the normotensive nonpregnant women [11]. On the other hand, endogenous nitric oxide production does not play an important role in the control of human term or preterm nonlaboring uterine smooth muscle contractility [12].…”
Section: Introductionmentioning
confidence: 91%
“…28 In addition, the NO signaling pathway, the vasodilator and antiplatelet effects of NO are expected to decrease vascular tone and increase placental blood flow, leading to better fetal nutrients and oxygen supply. 42 This expectation explains the increased fetal viability and birth weight in the MgSO 4 -treated group. The reduction of circulating antiangiogenic factors in the PRE þ MgSO 4 group in the current study could be explained by the ability of MgSO 4 to decrease systemic vascular resistance and counteract the vasoconstrictor substances in several vascular beds.…”
Section: Discussionmentioning
confidence: 94%
“…However, the physiological role of NO in pregnancy and follicular phase remains controversial owing to the lack of direct NO measurement (11,37,39). By simultaneously monitoring [Ca 2ϩ ] i and NO levels in the freshly isolated endothelium of UAs, we report the first direct evidence that pregnant, follicular, and L endothelial cells have different abilities to produce NO in response to pharmacological and physiological [Ca 2ϩ ] i agonists.…”
Section: Discussionmentioning
confidence: 98%